ANALISIS PEMBUKTIAN TERHADAP TINDAK PIDANA PENGHINAAN DALAM KONTEN YOUTUBE PADA PUTUSAN PENGADILAN JAKARTA SELATAN (STUDI KASUS PUTUSAN NOMOR 1327/PID.SUS/2019/PN JKT.SEL) - Rizky Setiawan; Ade Adhari (Jurnal Hukum Adigama, 2022)
The use of Youtube social media is often misused for purposes that violate the law or unwittingly thecontent uploaded contains criminal acts. One of these cases is Decision Number1327/Pid.Sus/2019/Pn Jkt.Sel or more virally known as the "salted fish" case in which the contentcontains content that violates decency and insults/defamation. The research problem emphasizes moreon how to apply evidence against criminal acts of humiliation through Youtube social media in thecase of decision Number 1327/Pid.Sus/2019/Pn Jkt.Sel? The method used is normative juridical withdeductive data analysis techniques. The application of evidence to prove the criminal act charged withremains refers to Article 184 of the Criminal Procedure Code regarding evidence, namely witnessstatements, expert statements, letters, instructions and statements of the defendant. In this case, theevidence submitted is the testimony of witnesses including victim/reporting witnesses, statements ofexperts, namely ITE experts and criminal law experts, as well as statements of the defendants. Forelectronic evidence and print outs. The indictment of Article 27 paragraph (1) the prosecutor wasunable to prove the existence of a moral violation charge so that the judge chose the primaryalternative indictment Article 27 paragraph (3) was proven as a criminal act of defamation and eachperpetrator was qualified as "a person who participated in committing" (mede pleger). Thegovernment and the legislature need to revise the ITE Law because there are many articles withmultiple interpretations that allow for wild interpretations to obscure the true meaning.